The notion of the “foreigner” in contemporary Greek drama: “We” through the faces of the “others” - Grigoriou, Rea (The Historical Review/La Revue Historique, 2020)
This article explores the dramaturgy of modern Greek playwrights, among others Vassilis Katsikonouris, Giannis Tsiros, Michalis Reppas, Thanasis Papathanasiou and Lena Kitsopoulou. It looks at how these dramatists approach the theme of “alterity” when in their dramatic productions it acquires the meaning of a different ethnic, religious, social and cultural element. It mainly reflects on the roles of the dramatic characters within the multiculturalist environment as it manifested in Greek society in the 1990s and at the beginning of the twenty-first century. The notion of “different” is also examined by drawing on political views of racist and nationalistic ideologies that emerge in the dramatic situations. The dramaturgical analysis is also comparatively combined with the way theatre reviewers and the audiences have received the productions, since the plays’ various interpretations by contemporary directors is considered of the utmost importance.